Hubungan antara Manajemen Konflik dan Kinerja Organisasi melalui Negosiasi pada Industri Manufaktur - Adi Neka Fatyandri; Mualifah Nurhidayati; Sheril Fitri Riana; Lusiana; Fenny; Moderin (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study is to determine the relationship between conflict management and organizational performance through negotiations in the manufacturing industry. The study reviews the relevant theoretical and empirical literature. Survey research techniques are adopted as research designs. The data used was sourced from primary sources as many as five manufacturing companies as samples in this study. The resulting data were analyzed using frequency tables and percentage analysis. The results showed that all conflict management strategies studied, namely negotiation, collective bargaining, joint consultation and alternative dispute resolution were found to have a significant positive relationship with organizational performance. The study concluded that conflict management has a significant positive relationship with organizational performance in selected brewery companies in Southeast Nigeria. The study recommends that managers should adopt conflict management strategies as they prove effective in managing conflicts within the organization.